Food Sanitation Situation in Primary School, Yala Primary Education Service Area 2 - ท่าดะ อำพร; อาบูวะ ซุรียาณี อาบูวะ; อาบูวะ ดารีนา อาบูวะ (YRU Journal of Science and Technology, 2018)
The objective of the research was to study the food sanitation surveillance situation in primary school, Yala Primary Education Service Area 2 and the results of the study are available suggestion for the school administrators . The sample is a school in Yala Education Service Area 2 Area 6 schools The research findings is take lunch and teacher in School is female and graduate A bachelor’s degree. The experience is the most trained nutritional 5 more times. the overview of general information about the nutritional quality is moderate. The nutrition plan at a high level. The nutrition operational is moderate. promoting the development of the nutrition at a high level. The monitoring nutrition is moderate and the evaluation nutrition is moderate. the standard of the food sanitation of the Department of Public Health, Ministry of Health’s cafeteria surveying the best school is moderate to very low and analysis coliform bacteria contamination in foods and containers for foods are contaminated with coliform bacteria maximum 87.5 percent ant the minimum 75.0 percent the rates are highly contaminated also considered criteria Schools and sanitation systems in much less children.The need to improve and solved urgently.